2014
DOI: 10.3389/fgene.2014.00064
|View full text |Cite
|
Sign up to set email alerts
|

Dietary interactions with the bacterial sensing machinery in the intestine: the plant polyphenol case

Abstract: There are millions of microbes that live in the human gut. These are important in digestion as well as defense. The host immune system needs to be able to distinguish between the harmless bacteria and pathogens. The initial interaction between bacteria and the host happen through the pattern recognition receptors (PRRs). As these receptors are in direct contact with the external environment, this makes them important candidates for regulation by dietary components and therefore potential targets for therapy. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 151 publications
(253 reference statements)
0
13
0
Order By: Relevance
“…Therefore, the flavan3-ols are absorbed by the enterocytes without any deconjugation or hydrolysis (88). On the other hand, flavonoids including flavonol-3-ols are generally recognized as xenobiotics by the intestinal detoxification system (92). Accordingly, they may be subjected to Phase II biotransformation (conjugation) in the enterocytes and posteriorly in the hepatocytes, resulting in a series of water-soluble conjugated metabolites including methyl, glucuronide, and sulfate derivatives (93).…”
Section: Intestinal Metabolism and Bioavailability Of Flavan-3-ols Anmentioning
confidence: 99%
“…Therefore, the flavan3-ols are absorbed by the enterocytes without any deconjugation or hydrolysis (88). On the other hand, flavonoids including flavonol-3-ols are generally recognized as xenobiotics by the intestinal detoxification system (92). Accordingly, they may be subjected to Phase II biotransformation (conjugation) in the enterocytes and posteriorly in the hepatocytes, resulting in a series of water-soluble conjugated metabolites including methyl, glucuronide, and sulfate derivatives (93).…”
Section: Intestinal Metabolism and Bioavailability Of Flavan-3-ols Anmentioning
confidence: 99%
“…Another disease that affects enterocytes is cholera, which generates an intracellular accumulation of cAMP that results in severe diarrhea (Crespy et al, 2002). It has been reported that polyphenols in the enterocyte favor increased production of SOD and GPx, which may constitute a form of cell protection (Ahmed-Nasef et al, 2014). The effect of oral administration of polyphenols from the apple in cases of acute diarrhea during cholera disease has been commented in the literature, showing that it can be used as a therapeutic and precautionary measure, by demonstrating the inhibition of cholera decreases ADP ribosylation and fluid accumulation induced by the toxin (Crespy, 2002).…”
Section: Intestinal Effectsmentioning
confidence: 99%
“…); (5) stimulating immunological defence; (6) creating a protective barrier; and (7) inhibiting the growth of potential pathogens (Gibson & Roberfroid ; Gibson ; Gong & Yang ; Ahmed Nasef et al . ; D'Argenio & Salvatore ; Okumura & Takeda ).…”
Section: Gut Health and The Host Gut Microbiotamentioning
confidence: 99%